Konsep pendidikan Islam dan Barat (Analisis komparatif Ibnu Khaldun dan Paulo Freire serta relevansinya dengan pendidikan Modern) - Icha Rezyika; Qolbi Khoiri; Iwan Sitorus Ramadhan (UIN Fatmawati Sukarno Bengkulu, 2025)
This study uses a qualitative method with a type of library research, while the data collection technique used is a documentation technique, namely collecting data from sources of notes, transcripts, books and so on. The results of the concept of Islamic and Western education with a focus on a comparative analysis between the thoughts of Ibn Khaldun and Paulo Freire, and their relevance to modern education, namely, Ibn Khaldun, a 14th-century Muslim scholar, is known for his deep thoughts on education rooted in moral, social and cultural values. He emphasized the importance of the environment in shaping the character and morals of individuals and understanding the relationship between education and the development of society. On the other hand, Paulo Freire, a 20th-century Brazilian educator, developed a critical education theory that emphasized the active participation of students in the learning process, as well as the importance of education for social empowerment and justice. By examining these two thoughts, this thesis aims to see the similarities and differences in their approaches to education, and how both concepts can contribute to modern education. The relevance of Ibn Khaldun and Paulo Freire's thoughts in the context of education today is very important, considering the global challenges faced by the world of education, such as inequality of access and quality of education. Therefore, this study is expected to provide new insights into the importance of integrating universal values in education to form individuals who are not only intelligent, but also have noble character and are critical of the social reality around them